An amphipathic Bax core dimer forms part of the apoptotic pore wall in the mitochondrial␣membrane. (8th June 2021) - Lv, Fujiao; Qi, Fei; Zhang, Zhi; Wen, Maorong; Kale, Justin; Piai, Alessandro; Du, Lingyu; Wang, Shuqing; Zhou, Liujuan; Yang, Yaqing; Wu, Bin; Liu, Zhijun; et al.
Abstract: Bax proteins form pores in the mitochondrial outer membrane to initiate apoptosis. This might involve their embedding in the cytosolic leaflet of the lipid bilayer, thus generating tension to induce a lipid pore with radially arranged lipids forming the wall. Alternatively, Bax proteins might comprise part of the pore wall. However, there is no unambiguous structural evidence for either hypothesis. Using NMR, we determined a high‐resolution structure of the Bax core region, revealing a dimer with the nonpolar surface covering the lipid bilayer edge and the polar surface exposed to water. The dimer tilts from the bilayer normal, not only maximizing nonpolar interactions with lipid tails but also creating polar interactions between charged residues and lipid heads. Structure‐guided mutations demonstrate the importance of both types of protein–lipid interactions in Bax pore assembly and core dimer configuration. Therefore, the Bax core dimer forms part of the proteolipid pore wall to permeabilize mitochondria. Synopsis: Bax proteins form giant pores in mitochondrial membranes to initiate cell death. Structural determination and activity analyses of membrane‐bound amphipathic Bax core dimers disambiguate their function as building blocks of the apoptotic pore wall. High‐resolution NMR analyses reveal the structure of the α2–α5 helices of Bax bound to a lipid bilayer. This Bax core region forms a symmetric dimer interacting with lipid bilayer with a 60° tilt angle, to cover both the nonpolar acyl tails and the polar phosphate heads. Both nonpolar and polar lipid contacts of the Bax core dimer dictate its configuration and pore forming activity in model bilayers as well as native mitochondrial membranes. Abstract : NMR structures of membrane‐bound Bax core dimer reveal dual interactions with non‐polar tails and charged heads of bilayer lipids contributing directly to apoptotic mitochondrial permeabilization.